A review of records and research actions for the Critically Endangered Beck's Petrel Pseudobulweria becki. Issue 3 (29th October 2013) - BIRD, JEREMY P.; CARLILE, NICHOLAS; MILLER, MARK G. R.
Summary: The "Critically Endangered" Beck's Petrel Pseudobulweria becki has been recorded regularly in the Bismarck Sea during the past five years, but its nesting grounds are yet to be located. Previously, over 70 years elapsed between the collection of the original specimens in 1928 and 1929, and the next confirmed observations in 2007. We evaluate over 40 documented records of the species as well as recorded survey effort within the Bismarck Archipelago and Solomon Islands and we assess potential breeding areas as well as land and sea priority search areas. On current evidence, southern New Ireland, within the Bismarck Archipelago, remains the highest priority area to search for nesting colonies but other parts of the region also warrant further investigation. The species's distribution, population size and trends, ecology and threats are all poorly known, so prescribing conservation actions is difficult. As a starting point we identify the most important research actions to advance current knowledge, recognising that locating the nesting grounds of the Beck's Petrel remains the prime conservation priority for this species.